2023
DOI: 10.1039/d2cp05456f
|View full text |Cite
|
Sign up to set email alerts
|

Selective etching mechanism of silicon oxide against silicon by hydrogen fluoride: a density functional theory study

Abstract: Selective etching of silicon oxide (SiO2) against silicon (Si) using anhydrous hydrogen fluoride (HF) vapor has been used for semiconductor device fabrication. We studied the underlying mechanism of the selective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We examined the mechanism of the HF gas-phase anisotropic etching of SiO 2 via the generation of gas-phase SiF 4 and H 2 O. According to the previously reported models in which the reaction of SiO 2 with HF was studied using computational simulations, ,, the reaction pathway of SiO 2 with HF gas using the novolac-type photoresists was investigated via DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the mechanism of the HF gas-phase anisotropic etching of SiO 2 via the generation of gas-phase SiF 4 and H 2 O. According to the previously reported models in which the reaction of SiO 2 with HF was studied using computational simulations, ,, the reaction pathway of SiO 2 with HF gas using the novolac-type photoresists was investigated via DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas 19,20 On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. 21,22 In the present work, CF 4 and HF plasma discharges diluted with H 2 were utilized to etch the SiN films prepared by plasmaenhanced chemical vapor deposition (PECVD). To elucidate the role of hydrogen, the chemical properties of the CF 4 /H 2 and HF/H 2 plasmas were investigated by means of optical emission spectroscopy and optical actinometry techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has also been reported that high SiN/SiO 2 selectivity can be achieved using gas mixtures such as NF 3 /O 2 or CF 4 /N 2 /O 2 plasmas, which is attributed to the influence of NO radicals. , The addition of hydrogen to fluorocarbon gas, leading to the generation of CH x F y ions, can be used to enhance the etch rate (ER) and/or selectivity of SiN/SiO 2 or SiN/Si. Special hydrofluorocarbon gases have been used to achieve high etch selectivity for SiN over SiO 2 and Si. Additionally, the dependence of selectivities between Si-based materials on substrate temperature has recently been investigated by various research groups. , In hydrogen-contained fluorocarbon plasmas, the formation of hydrogen fluoride (HF) is anticipated to have a detrimental effect on etching for Si-based materials, as it tends to scavenge F radicals . In the mechanism of SiN etching, the H also reacts with N and CF x species, resulting in the formation of HCN as a byproduct, which helps to reduce the FC polymerization and facilitates the progress of SiN etching. , Based on the experimental and simulation results, it has been reported that HF molecules appear to play an important role in the selective etching of SiN over SiO 2 in NF 3 /N 2 /O 2 /H 2 remote plasmas , On the other hand, recently, there have been investigations into the selective etching of SiO 2 over SiN or Si using an HF vaper, employing both computational simulations and experimental approaches. , …”
Section: Introductionmentioning
confidence: 99%